Finding the optimum level of wavelet decomposition for reducing noise in wireless communication - Omar S.F.; Yussof S.; Islam T. (2023)
This paper presents an experiment to find the optimum level of wavelet decomposition for time-frequency analysis in wireless communications. Wavelet decomposition is used in many applications to reduce noise in transmitted signals in wireless communications. However, there are problems to obtain optimum level of wavelet decomposition for reducing noise in practice. This work is shown in the design of finding optimum level of wavelet decomposition including signal to noise ratio (SNR) in computers based simulations. Numerical results obtained from analysis and simulations shows how very good performance is obtained with optimum level of wavelet decomposition. The model of finding optimum wavelet decomposition has the advantages of flexibility, efficiency, and accuracy of using wavelet transformation in wireless communications.